Blockchain-enabled solutions for the pharmaceutical industry - Wason, Ritika; Arora, Parul; Nand, Parma; Jain, Vishal; Kukreja, Vinay (John Wiley & Sons, Inc. ; Scrivener Publishing LLC, 2025)
The 25 chapters in this volume serve as a comprehensive guide to understanding and implementing blockchain-enabled solutions in the pharmaceutical industry. The pharmaceutical industry is undergoing a holistic transformation, where innovation is key to addressing complex challenges and enabling user-centric, customized services. This book explores the potential applications of blockchain technology in revolutionizing pharmaceutical processes. By integrating blockchain fundamentals, the pharmaceutical industry can enhance transparency, security, and efficiency in areas such as supply chain management, patient safety, and more. Blockchain can also improve regulatory compliance, streamline clinical trials, and protect data integrity. Furthermore, it enables secure transactions, reduces the prevalence of counterfeit drugs, and strengthens patient privacy and data management. Some of the subjects readers will find the volume covers include: How blockchain technology can revolutionize the healthcare sector by enabling a secure, decentralized, and tamper-proof system for handling patient data, and facilitating seamless information sharing across various healthcare providers - how blockchain transforms the pharmaceutical industry by enhancing drug traceability, ensuring product authenticity, and reducing counterfeit drugs - a comprehensive blockchain-based framework to improve the pharmaceutical supply chain from manufacturers to end consumers - how the Pharma-RBT solution utilizes blockchain technology to protect personally identifiable information (PII) during drug trials - the use of blockchain-based smart contracts to automate and streamline payment processes reducing transaction times and minimizing human errors - surveys how blockchain can ensure the validity of pharmaceutical products by providing an immutable and transparent ledger that tracks each phase of a drug's lifecycle, from production to the end consumer - how blockchain can enhance the security of smart medicine vending machines - how blockchain can improve the kidney transplantation process by enhancing the security, traceability, and efficiency of donor-recipient matching, organ transportation, and post-operative care - how blockchain can contribute to the development of the metaverse by enabling decentralized ownership of virtual assets - how blockchain can improve clinical trials by enhancing transparency, efficiency, and ethical conduct in drug development - how blockchain technology can revolutionize the drug recall process - how integrating hybrid technologies with blockchain can enhance smart healthcare systems - how the metaverse can transform healthcare by offering immersive virtual environments for medical training, patient education, and remote consultations. Audience The book will appeal to researchers, scientists, and professionals in the biomedical and pharmaceutical industries, as well as computer scientists and experts in blockchain technology, cybersecurity, and logistics.
Description based upon print version of record.
Keywords: Pharmaceutical industry -- Technological innovations.; elektronické knihy; electronic books